PENGARUH SUBSTITUSI TEPUNG BENGKUANG (PACHYRIZUS EROSUS) TERHADAP KUALITAS CHOCOCHIP COOKIES: Studi Eksperimental terhadap sifat Organoleptik Chocochip Cookies hasil substitusi tepung bengkuang - Suprihartini, Dwiyani; Faridah, Anni; Kasmita; Adriani, Cici (Pasundan Food Technology Journal (PFTJ), 2025)
This research aims to determine the effect of yam bean flour (Pachyrhizus erosus) substitution on the quality of Chocochips Cookies. The study applied a Completely Randomized Design (CRD) with four treatments (0%, 20%, 40%, and 60%) and three replications. Organoleptic and hedonic tests were conducted on 50 panelists to evaluate shape, color, texture, aroma, and taste. The results showed that yam bean flour substitution up to 60% did not significantly affect the quality of shape, color, and texture. Meanwhile, aroma and taste exhibited significant differences at the 5% significance level; however, Duncan’s test indicated no real differences among treatments. Therefore, yam bean flour can be used as a partial substitute for wheat flour in Chocochips Cookies as an alternative low-gluten product utilizing local ingredients.